The study of consistent properties of the vasopressin nasal dosage form - Al Nukarii Abdulkarim; A. L. Drozdov; A. P. Lysyanskaya (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Evaluation of consistent properties is an important and integral part of investigations on the creation of semisolid nasal pharmacotherapeutic agents.